Effect of Dextran on Experimental Venous Thrombosis in Rabbits - Ah-See, A.-K; Arfors, K.-E; Bergqvist, D; Tangen, O (Thrombosis and Haemostasis, 1974)
An experimental model combining controlled stasis and endothelial destruction by sodium morrhuate has been used to investigate the effect of dextran on venous thrombus formation in rabbits. Dextran 70 (1 g/kg body weight in a 10% solution), given 3 hours before thrombosis induction, significantly reduced the incidence of venous thrombosis when compared to a saline control. Dextran 40 (1 g/kg body weight in a 10% solution) and dextran 70 (0.6 g/kg body weight in a 6% solution) had no significant effect under these conditions. When given 10 or 120 minutes before initiation of thrombosis none of the dosages of dextran had any preventive effect. The results indicate that the haemodynamic effects of dextran were not involved in its preventive effect in this study. The effect of dextran was probably due to a combination of an effect on platelet reactivity and a change of the structure of fibrin formed during growth of the thrombi.